Recent progress in cassava agronomy research in Thailand - Tongglum, Anuchit; Pornpromprathan, V.; Paisarncharoen, K.; Wongviwatchai, C.; Sittibusaya, C.; Jantawat, Somjate; Nual-on, T; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 1998)
Cassava agronomy research in Thailand during 1994-1996 emphasized mainly erosion control, soil fertility maintenance and weed control. Regarding soil erosion control, the planting of cassava in April, at the start of the rainy season, and harvesting in March resulted in the highest soil loss compared with other planting dates. Planting at the start of the dry season in Dec and harvesting in Nov produced by far the highest cassava yield, while soil loss due to erosion was relatively low. Intercropping cassava with either peanut or pumpkin were found to be the best cropping systems to reduce erosion while also giving high gross incomes. Cassava planted on contour ridges at closer spacing (1.0x0.6 m) and with fertilizer application was the most promising package of cultural practices for reducing erosion and increasing yields.